Nanoparticle Notch Filters for Selective Filtering of Blue Light in Contact Lenses - Krishnakumar, Harish (University of Waterloo, 2018)
The visible wavelengths are essential to a normal colour vision, however overexposure of high-energy visible (HEV) light may be damaging to both ocular and non-ocular health. Some health concerns associated with HEV light (commonly referred to as blue light) include retinal damage, age-related macular degeneration (AMD) and photophobia in benign essential blepharospasm (BEB) and migraine patients. Certain wavelengths of blue light are essential to regulating bodily functions such as pupillary light reflex, melatonin regulation, and circadian rhythm, therefore completely filtering out these wavelengths may have adverse health effects. Despite its health impact, there is a severe dearth of blue light filtering eyewear that provide adequate protection from harmful blue-light wavelengths while allowing beneficial wavelengths of blue light to be transmitted. Contact lenses are an attractive platform for incorporating blue-light filters. There are currently over 71 million contact lens wearers worldwide, however there are currently no commercially available contact lenses on the market offering both UV and blue light protection. This thesis presents a novel approach to selectively filtering out blue-light wavelengths in contact lenses through the use of plasmonic silver nanoparticles (AgNPs). First, a tunable synthesis process was developed to allow for the production of AgNPs with customizable localized surface plasmon resonance (LSPR) peaks between 400 – 450 nm and full width at half maximum (FWHM) values of less than 45 nm. Next, the blue-light filtering AgNPs were encapsulated with a thick, uniform layer of silica to preserve colloidal and optical stability as well as minimizing leaching of Ag+ ions. Lastly, the silica-coated AgNPs were integrated into commercial etafilcon contact lenses using industry transferrable processes. The NP-integrated lenses demonstrated blue-light filtering capabilities while being transparent in the visible wavelengths. In addition, the NP-integrated lenses demonstrate stability post-autoclaving, UV and natural sunlight exposure, and room temperature storage.
Keywords: Plasmonic nanoparticles; contact lenses; blue light; notch filters